Teacher well-being in change: a quantitative analysis of schoolteachers’ approaches to teaching and their teaching-related well-being during rapid shift in their work environment - Lahdenperä, Juulia; Postareff, Liisa (Routledge, Taylor & Francis Group, 2025)
Pedagogical training often aims to solicit changes in teachers’ pedagogical behaviour. However, previous studies have demonstrated that these endeavours are time-consuming and challenging. In the present study, we used the opportunity created by the COVID-19 pandemic to investigate how comprehensive schoolteachers’ approaches to teaching change in response to rapid contextual changes and how these changes in teaching behaviour are connected to teachers’ teaching-related well-being. Quantitative data were collected from schoolteachers in one Finnish municipality (N = 116). The results indicate that changes in pedagogical behaviour challenge teaching-related well-being, implying that teacher well-being is an important aspect to consider in teacher education and pedagogical training. Furthermore, the results demonstrate a high level of intrapersonal contextual variation in approaches to teaching, highlighting the importance of contextual perspectives in future investigations of teachers’ pedagogical behaviour.